Mandatory and Voluntary Disclosure of Annual Report on Investor Reaction - Hendra Gunawan; Evelyn Octa Lina (International Journal of Economics and Financial Issues, 2015)
This study aims to obtain empirical evidence about the influence of mandatory disclosure, voluntary disclosure on investor reaction to either partially or simultaneously. The study was conduct on 38 manufactured companies listed on Indonesian Stock Exchange. There are five variables that mandatory disclosure, voluntary disclosure as the independent variable, cash flow operating activities (AKOp), cash flows investing activities (AKIn), cash flows financing activities (AKDa) as the control variable and the investor reaction was measured by using trading volume activity as the dependent variable. The result indicates that mandatory disclosure partially affect the investor reaction mandatory disclosure, voluntary disclosure simultaneously affect the investor reaction. Limitations are mandatory disclosure, voluntary disclosure, cash flow operating activities (AKOp), cash flow investing activities (AKIn), cash flow financing activities (AKDa) are less able to measure the volume of stock trading prediction of the future